A CROSS-SECTIONAL STUDY FOR EVALUATION OF SELECTED EPIDEMIOLOGICAL FACTORS LINKED TO HYPERTENSION IN TRUCK DRIVERS - Dixit, Srishti; Gupta, Sachin (Journal of Biomedical and Pharmaceutical Research, 2020)
Background: The nature of their profession and the workplace they operate in puts truck drivers at an increased risk of cardiovascular disorders like hypertension. Objectives: Examine the chosen epidemiological variables linked to hypertension and gauge your understanding of the importance of exercise and a healthy diet in regulating blood pressure. Methodology: This cross-sectional study was carried out in the central Indian market known as the Agricultural Produce Market Committee (APMC). Results and discussion: The average age of truck drivers was 34 years old, and they had been driving for 6 years on average. There was a strong correlation identified between BMI and hypertension. Stage 1 and stage 2 hypertension were both prevalent in truck drivers, accounting for 45% of the population. Conclusion: Numerous factors, including obesity and addiction, which are more prevalent in truck drivers, may be to blame for their hypertension. Truck drivers may also have hypertension due to a number of other issues, including inadequate sleep, an improper diet, and insufficient exercise. Key words: Truck drivers, hypertension, Body mass index, Addiction, exercised.